Development of a healthy snack for children with HIV/AIDS or compromised immunity - Erasmus, Valerie (My University, 2010)
Background - Human Immunodeficiency Virus (HIV) is the virus that causes the disease Acquired Immunodeficiency Syndrome (AIDS). the IV/AIDS epidemic in Sub Saharan Africa (SSA) has already orphaned a generation of children, and it is projected that by 2010, 18 million African children under the age of 18 years are likely to be orphans (Andrew, Skinner & Zuma 2006:269-276). In 2005 approximately 4.1 million people died of AIDS-related illnesses. A common consequence of HIV/AIDS infection is malnutrition and weight loss, which is used as a diagnostic criterion for HIV/AIDS. the relationship between HIV/AIDS and malnutrition and wasting is well desccribed, with nutritional status compromised by reduced food intake, malabsorption caused by gastrointestinal involvement, increased nutritional needs as a result of fever and infection and increased nutritional losses. Malnutrition contributes to the frequency and severity of the opportunistic infections seen in HIV/AIDS and nutritional status is a major factor in survival. Failure to maintain body cell mass leads to death at 54 percent of ideal body weight. The effectiveness of nutrition intervention has been documented and counselling in dietary nutrition is considered critical in the treatment of HIV/AIDS. Objective - The main objective of this study was to determine the nutritional status of the HIV/AIDS-affected or immunity compromised children attending a care centre in Boipatong in order to develop an energy bar to address malnutrition in these children. Methodology - This was an experimental study carried out in four phases. The planning of the study constituted the first phase. In the second phase a baseline survey was conducted, in which a socio-demographic questionnaire (n=45) was administered amongst children aged six to 13, with the assistance of trained fieldworkers. Dietary intake was measured by a 24-hour recall and Food Frequency Questionnaire (FFQ) and anthropometric measurements included height and weight. The data from the socio-demographic questionnaires and FFQ were captured on an Excel spreadsheet. The Statistical Package for Social Sciences (SPSS) for Windows version 15.0 program was used to analyse the data. Descriptive statistics were used (frequencies, means and SD. The 24-hour recall was analysed for means and Standard Deviation (SD) of nutrient intakes on the FoodFinder program version 3.0 and compared to Dietary Reference Intakes (DRI). The anthropometric measurements were analysed using the WHO growth standards (2007). Phase 3 incorporated the development of the snack bar, sensory evaluation, microbiological tests for shelf life determination and chemical analyses to determine nutrient content. Phase 4 entailed the writing of the report. Results - In the baseline survey the results indicated that this was a low-income community with compromised nutrtion, mainly under-nutrition owing to poor dietary intake despite a good variety of foods in the diet. All the households included in this study were resident in Boipatong and the majority (86.5 percent) have lived in Boipatong for longer than five years. although the majority of respondents resided in brick houses (69 percent), only 30 percent had access to water inside and outside their houses, 23.1 percent had access to water, 78.4 percent had access to electricity and 75 percent had regular waste removal. The percentage of unemployed among the children's caregivers was high (60.9 percent) and the majority of households (40 percent) had an income on R500-1000 per month, with two contributors of household income in 57 percent of the households. Although the average household consisted of five people, the houses were relatively small with 75 percent of all the households having four or more rooms. All of the households experienced problems such as rodent and insect infestation. The household food security was also a dilemma in this community as 70.6 percent of the respondents indicated that they bought food only once a month and the majority of households spent less than R150 (5.4 percent of household income) on food per month i.e. less than R37.50 per week. The anthropometric results indicated 29 percent stunting, and 23 percent underweight among the boys in the target group, compared to 30 percent and 0 percent for the girls respectively. The criteria applied in developing the snack food were to achieve at least 25 percent of vitamin A, vitamin C, Vitamin E, certain B-group vitamins and minerals such as selenium, zinc and iron to meet the recommended dietary allowances (RDA). Since the results showed that 67 percent of households had an electrical stove, an easily prepared recipe was formulated which could be taught to the caregiver. Moreover, at R1.50 per person per day, the product was cost-effective and proved safe as well as acceptable to the children, thus ensuring compliance when the feeding intervention is implemented. The sensory evaluation of the snack item showed that it was acceptable to the majority of the children as it received a high score for taste, general appearance and overall acceptability. The snack food item was tested for shelf life and the results showed a shelf life of 168 days in a refrigerator and a recommeded shelf life of 21 days at room temperature (30 C). Conclusions and recommendations - The results indicated that poverty, household food insecurity and malnutrition were prevalent in this community. Furthermore, the study proved that a product could be developed to meet specific criteria. It is recommended that this product be tested in a clinical intervention study to determine the impact on the nutritional status of children with compromised immunity.
Thesis. (M.Tech. (Food Service Management, Dept. of Hospitality and Tourism and PR Management))--Vaal University of Technology, 2009.
Keywords: HIV affected children--Nutritional status; AIDS affected children--Nutritional status; Snack food; Healthy snacks for children